Blakea alatibracteata (Pyxidantheae, Melastomataceae), a new enantiostylous species from Colombia, with an elaboration of the wet bud clade - Penneys, Darin S.; Almeda, Frank; Urrea, Johan; Burns, Connor (Phytotaxa, 2026)
Blakea alatibracteata is described as a new species from Chocó and Valle del Cauca, Colombia. This novelty is readily distinguished from closely related species within the wet bud clade by its long-decurrent, winged outer floral bracts. Only two other members of the genus, B. attenboroughii and B. mcphersonii, have similar outer floral bracts, but neither have calyx lobes and calyx tubes with anastomosing veins, anther connective appendages that are paired, elongate humps, nor capitate stigmas, all of which are putative synapomorphies of the wet bud clade. For B. alatibracteata, an illustration, photo plate, distribution map, recommended conservation assessment, and discussion of related species based on morphological similarities are provided. A thorough description of the Blakea wet bud clade morphological characteristics, and a key to its 11 species, are also included.